Bioinspired Crosslinked Nanocomposites of Polyvinyl Alcohol-Reinforced Cellulose Nanocrystals Extracted from Rice Straw with Ethanedioic Acid. (4th July 2022) - Chin, Kwok-Mern; Sam, Sung Ting; Ong, Hui Lin; Wong, Yee Shian; Tan, Wai Kian; Vannaladsaysy, Vilay
Abstract : In this study, cellulose nanocrystals (CNC) were extracted from rice straw and incorporated into polyvinyl alcohol (PVOH) as reinforcement nanofillers. Multiple nanocomposites with different CNC contents were prepared. Extracted CNC appear as long, well-defined rodlike crystals with a high aspect ratio (41). Nanocomposites with 3 wt% of CNC significantly exhibit improved tensile strength (60.4%) and maximum degradation temperature (287°C). Moreover, they demonstrate a decrease in water vapor permeability rate and in the swelling and solubility indices of PVOH/CNC. Significant improvements were observed when nanocomposites were crosslinked specifically in terms of tensile strength (104.8%) and maximum degradation temperature (364°C). They also demonstrate greatly reduced water vapor permeability rate, swelling, and solubility indices. The optimum CNC amount for both nanocomposites is 3 wt%.